Network+ certification study guide (Osborne McGraw-Hill, 1998)
Though intimidating at first glance, all misgivings fall away once you begin traversing the pages of the Network+ Certification Study Guide. This book is laid out exceptionally well, with each chapter divided into certification objectives such as network operating systems, network protocols, and password practices and procedures.